2008
DOI: 10.2967/jnumed.107.047381
|View full text |Cite
|
Sign up to set email alerts
|

Small-Animal PET Imaging of Human Epidermal Growth Factor Receptor Type 2 Expression with Site-Specific 18F-Labeled Protein Scaffold Molecules

Abstract: Human epidermal growth factor receptor type 2 (HER2) is a wellestablished tumor biomarker that is overexpressed in a wide variety of cancers and that serves as a molecular target for therapeutic intervention. HER2 also serves as a prognostic indicator of patient survival and as a predictive marker of the response to antineoplastic therapy. The development of 18 F-labeled biomolecules for PET imaging of HER2 (HER2 PET ) is very important because it may provide a powerful tool for the early detection of HER2-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
121
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(127 citation statements)
references
References 18 publications
5
121
0
1
Order By: Relevance
“…Unlike Affibody molecules labeled using residualizing radiometal labels 22,23,32,35 , the renal retention of 18 F-N-(4-fluorobenzylidine)oxime-labeled Affibody molecules is quite low (Figure 9). This is in agreement with data showing rapid clearance of radioactivity from kidneys for other Affibody molecules labeled with 18 F-N-(4-fluorobenzylidine)oxime 19,29,30 . This is a strong indication that the Experiments in tumor-bearing mice confirmed that 18 F-FBO-E 3 -PEP4313 can target HER2-expressing xenografts with high specificity (Figure 8).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Unlike Affibody molecules labeled using residualizing radiometal labels 22,23,32,35 , the renal retention of 18 F-N-(4-fluorobenzylidine)oxime-labeled Affibody molecules is quite low (Figure 9). This is in agreement with data showing rapid clearance of radioactivity from kidneys for other Affibody molecules labeled with 18 F-N-(4-fluorobenzylidine)oxime 19,29,30 . This is a strong indication that the Experiments in tumor-bearing mice confirmed that 18 F-FBO-E 3 -PEP4313 can target HER2-expressing xenografts with high specificity (Figure 8).…”
Section: Discussionsupporting
confidence: 81%
“…In fact, 18 F-fluorobenzaldehyde conjugation has been used for labeling of recombinant dimeric 19 and monomeric 29 anti-HER2 Affibody molecules (after conjugation of 2-…”
Section: Introductionmentioning
confidence: 99%
“…Chemical modifications with polyethylene glycol (PEG) or albumin binding peptides have been used to increase circulation time and enhance pharmacokinetic profiles (Chen et al 2004b). In addition, peptides with higher target binding affinity (Kimura et al 2009a) and multivalent target binding (Liu 2006) have been shown to elicit increased imaging signals compared to weaker binding and monomeric peptides; yet, in some cases monovalent proteins have been shown to exhibit better tumor uptake compared to higher affinity dimeric versions (Cheng et al 2008). The latter observation is interpreted to result from the effects of molecular size on tissue diffusion.…”
Section: The Process Of Developing Phage-derived In Vivo Molecular Immentioning
confidence: 77%
“…Initial clinical studies in human patients with these ErbB2-targeting affibody molecules, labeled with 111 In for SPECT imaging or 68 Ga for PET imaging, have also been reported (Baum et al 2006). In another study, oxime conjugation chemistry was used to prepare ErbB2-specific monomeric and dimeric affibody molecules labeled with 18 F for PET imaging (Cheng et al 2008). Unexpectedly, the monomer showed better in vivo performance despite the higher ErbB2 binding affinity of the dimer (Figure 3).…”
Section: Molecular Imaging Agents Obtained Using Purified Targetsmentioning
confidence: 99%
“…Measurements of estrogen receptor expression by using [ 18 F]fluoroestradiol PET could be useful for stratifying breast cancer patients for estrogen-based therapy (9,10). PET using [4-18 F]fluorobenzaldehyde-conjugated aminooxy-protein scaffolds has been used in small animal models to detect tumoral Her2 expression (11). Similar approaches could guide the selection of chemotherapy regimes.…”
mentioning
confidence: 99%